A Prospective cohort study on cellulitis in adult patients with analysis of the factors related to the response to treatment. - Kumar, Mukesh; Roy, Vivek Kumar; Priya, Swati; Dev, Anand; Gopal, Krishna; Arun, Nidhi (Student's Journal of Health Research Africa, 2025)
Background The hallmarks of cellulitis include heated, red, and swollen purulent or non-purulent skin patches that can develop into more serious issues like sepsis and lymphedema. Cellulitis can strike anyone at any age, but it is more frequent in middle-aged and older people, with a small male preponderance. Objectives- The goal of this research is to clarify the many factors that affect how well cellulitis treatments work. Materials and methods Patients with cellulitis diagnosed between May 2022 and April 2023 were the subjects of this prospective observational study, which was carried out at the Department of General Surgery, Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, India. The study included 100 individuals in total. Results Among 100 patients with cellulitis, factors such as age ≥65 years, diabetes, leg and foot location, and abscess formation were significantly associated with poor treatment response. Abscess formation showed the strongest association, with a nearly threefold higher risk (OR: 2.8, p<0.05). Imaging findings like venous insufficiency also predicted poor outcomes. The logistic regression model demonstrated good predictive accuracy with an AUC of 0.77. Conclusion The significance of a thorough strategy that takes into account patient demographics, co-morbidities, clinical characteristics, microbiological variables, and imaging results when customizing treatment for cellulitis is highlighted by this study. It emphasizes how important focused interventions are to enhancing treatment results, particularly for high-risk patients. Recommendation Multicenter studies with larger sample sizes are recommended to validate these findings and improve generalizability.